ASSESSMENT OF BEST PARENTS AND SUPERIOR CROSS COMBINATIONS FOR EARLINESS RELATED TRAITS IN UPLAND COTTON (Gossypium hirsutum L.) - A. Shakeel; S. Ahmad; M. Naeem; T. A. Malik; M. F. Saleem; S. Freed (Journal of Animal and Plant Sciences, 2012)
A genetic analysis was conducted to determine the combining ability potential of six diverse Gossypium hirsutum L. genotypes and their 15 crosses for days to squaring, days to flowering, vertical flowering interval, horizontal flowering interval, days to first boll opening, boll maturity period, node number for first fruiting branch, height of first fruiting branch, mean maturity date and earliness index. Out of the six parents CIM-448 was found to be best general combiner followed by FH-945 and MNH-93 while CIM-496 was found to be poorest general combiner among the six parents. FH-945 × NIAB-78 proved to be best cross combination for various earliness traits followed by FH-945 × CIM-496, MNH-93 × CIM-446, MNH-129 × CIM-496. There is inference of predominant presence of non-additive type of gene action for all of the traits except DFF and HFFD. The plant material studied here is might be best suitable for hybrid breeding experiments.
Keywords: Cotton; specific combining ability; general combining ability; gene action